AN ALIEN LANGUAGE IN THE HOME DOMAIN: A CASE STUDY OF A CHILD WHO CANNOT SPEAK THE PARENT’S LANGUAGE - Siwi Tri Mawarni (LET: Linguistics, Literature and English Teaching Journal)
Children are the best learners of language because they can hear and distinguish all sounds. Interestingly, children can no longer speak their first language and then lose the first language (Indonesian). However, she speaks English as a second language while their parents cannot speak English. This study aims to reveal how this could happen and how she communicates with interlocutors in the home domain. The qualitative method was employed through the Interview with the participating individuals to gain specific information. The result shows that because of factors of age and the role of technology. The finding is Ag, 7 years old, could speak Indonesian. Because of the role of technology and almost every day she watched videos on YouTube, she began slightly lost the ability to speak Indonesian. Moreover, the findings also reveal how she communicates with interlocutors in the home domain who are not native speakers using verbal and nonverbal communication. The finding suggests that children learn new languages is good. However, parents do not forget to always communicate with their children using their parent language not to lose their first language